High-Grade Gliomas Diagnosis and Treatment - Barnett, Gene H.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
This is truly an exciting time in the field of neuro-oncology, particularly in the area of hi- grade gliomas. The management of patients with high-grade gliomas has historically been one of the most challenging and disheartening fields in medicine, where failure is the rule and longevity is the exception. The jaded often state that despite purported advances in surgical and radiotherapeutic techniques and a myriad of clinical trials of medical therapies, the s- vival statistics for glioblastoma have not changed in the last three decades. The nihilism associated with these tumors is such that some practitioners still advise against treatment or even biopsy, recommending palliative care with the diagnosis based only on history and an MRI scan. If the current state-of-the-art in the diagnosis and management of high-grade gliomas was truly so bleak, there would be no reason to compile and publish a monograph on the subject. The fact is that we have recently entered an era where real progress is being made in our understanding and treatment of high-grade gliomas that is directly benefiting some patients. We are slowly but surely chipping away at this problem. One approach has exploited correlations between particular molecular markers and therapeutic response. The first such “breakthrough” in high-grade glioma was the observation that loss of chromosomes 1p and 19q uniformly predict chemosensitivity in anaplastic oligodendrogliomas (1).
Classification of High-Grade Glioma -- Histologic Classification of High-Grade Gliomas -- Molecular Classifications -- Clinical Characteristics -- Pediatric High-Grade Glioma -- Adult High-Grade Glioma -- Diagnostic Tools for High-Grade Glioma -- Computerized Tomography -- Magnetic Resonance Imaging -- Magnetic Resonance Spectroscopy -- Imaging Tumor Biology -- Nuclear Imaging of Gliomas -- Magnetoencephalography -- Management -- General Considerations -- Surgical Techniques -- Radiation Therapy -- Brachytherapy -- Radiosurgery -- Chemotherapy -- Nursing Considerations -- Contemporary Investigational Treatments -- Convection-Enhanced Delivery -- Immunotoxins for Glioma Therapy -- Small Molecule Agents -- Cytokine Immuno-Gene Therapy for Malignant Brain Tumors -- Monoclonal Antibodies -- Clinical Trials of Oncolytic Viruses for Gliomas -- Biological Modifiers -- Gene Therapy -- Boron Neutron Capture Therapy of Brain Tumors -- Photodynamic Therapy.
Keywords: Neurosurgery; Oncology .; Neurosurgery; Oncology